Strategi Komunikasi Interpersonal Bidang Perlindungan dan Jaminan Sosial dalam Penyelesaian aduan Ketidaselarasan Data DTKS di Pelayanan Publik Kabupaten Tuban - Naufal Ahnaf Amrulloh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2025)
This study was motivated by the continued existence of public complaints regarding the inconsistency of DTKS (Data Terpadu Kesejahteraan Sosial) in the provision of Perlindungan dan Jaminan Sosial (Linjamsos) services in kabupaten Tuban. The lack of synchronization of data between the village, regency, and central governments often confuses and reduces public trust in social services. The purpose of this study is to explore the interpersonal communication strategies used by Linjamsos officers in handling public complaints. The research method used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation, as well as Miles and Huberman's interactive analysis with data validity tested through source triangulation. The results of the study indicate that empathy, openness, active listening skills, and adaptive communication are the main strategies that are effective in reducing conflict and rebuilding public trust. The research recommendations emphasize the importance of improving the communication capacity of officers, transparency of information, and cross-level government coordination to strengthen the quality of public services.